How Does Trade Respond to Anticipated Tariff Changes? Evidence from NAFTA - Khan, Shafaat Yar (World Bank, Washington, DC, 2021)
Firms anticipate upcoming tariff changes by shifting their purchases to periods with lower costs. This paper shows that such anticipatory dynamics overstate the trade elasticity. Standard identification of the trade response to trade cost changes uses tariff variation from free trade agreements and assumes that trade flows equal their consumption. However, free trade agreements eliminate tariffs gradually through announced phaseouts. This allows firms to delay their purchases until tariff cuts are effective, while consuming their inventories. Indeed, during the North American Free Trade Agreement’s staged tariff reductions, imports experienced sizable anticipatory slumps followed by libseralization bumps. To study the behavior of consumed imports, a measure is constructed that uses inventory-to-sales ratios to smooth the trade flows. Its application to the data yields that the annual trade-flow elasticity is 56 percent larger than the trade-consumption response and that the ratio of the long- to short-run elasticity increases from 2.3 with trade flows to 3.4 with consumed imports. The measure is validated through Monte Carlo simulations of an (s,S) ordering model that reproduces the observed trade pattern.